Justification of endolifting in laparoscopic surgery on the kidney (experimental research) - Grygorenko, V. M.; Baydo, S. V.; Pryndiuk, S. I.; Deneka, Y. R. (Journal of Education, Health and Sport, 2016)
Grygorenko V. M., BaydoS. V., Pryndiuk S. I., Deneka Y. R. Justification of endolifting in laparoscopic surgery on the kidney (experimental research). Journal of Education, Health and Sport. 2016;6(9):531-538. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154739 http://ojs.ukw.edu.pl/index.php/johs/article/view/3875 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 21.09.2016. JUSTIFICATION OF ENDOLIFTING IN LAPAROSCOPIC SURGERY ON THE KIDNEY (EXPERIMENTAL RESEARCH) V. M. Grygorenko2, S. V. Baydo1 , S. I. Pryndiuk1,2, Y. R. Deneka1 1LISOD – Israeli Oncological Hospital , Kyiv, Ukraine 2Public institution «Institute of Urology», Kyiv, Ukraine In the experiment at 8 human corpses the effectiveness of the original model of spiral laparolift and traditional methods of carboxyperitoneum during laparoscopic surgeries for kidney and upper urinary tract have been compared. The offered model of laparolift creats satisfactory intra- and extracorporeal spatial relationships between laparolift, tools and object of surgery, practically does not restrict freedom of extracorporeal movements of handles of working tools and laparoscope. The study showed that the availability of the surgery object, as working space in both the abdominal cavity and outside at the application of this laparolift are quite sufficient for laparoscopic surgery on the kidney. The positive results of the pilot study allowed successfully perform laparoscopic gas free surgeries on the kidneys (nephrectomy, resection) and upper urinary tract (pyeloplasty) in clinical practice, especially in patients with contraindications to surgeries in conditions of carboxyperitoneum Keywords: laparolift, endolifting, intense carboxyperitoneum, gasless laparoscopy.